Places of Memory in the Red Vyborg of 1918 - Fingerroos, Outi (Journal of Ethnology and Folkloristics, 2023)
The Karelian Isthmus belonged to Finland until 1939. The period between the World War I and the World War II was a time of rapid contextual change and ended the difficulties caused by modernisation aggravated in the year 1918. Divine-like authorities were posed in a new light and the Civil War of 1918 set the whole na- tion before direct aggression and “Red” revolutionism. The ”Whites” won the war at the expense of the ”Reds”. Young nation (Finland gained independence in 1917) was compelled to define its relation to Reds and Whites – Whites were chosen. Also the Lutheran church was officially against Red anarchy and bolshevism. The situation around the reminiscence concerning the Red victims of the Civil War 1918 in Finland is complicated. The question of the problem of meaning and pub- licity plays a central role in the logic concerning the ritual performance and memory of the Civil War 1918 in the city of Vyborg. There is public and private silence and even prohibition to be connected with deaths, memory and places. It has continued until these days. At the same time the official history was put on a favourable form and there were clear limits for the official narratives. The victory of the “Whites” was interpreted as a victory for the independence of the Finnish nation. The history of the “Reds” became a national anomaly: forgotten and invisible. The atmosphere of concealing continued until the 1960s, when especially Finn- ish literature took pioneer steps towards the more open minded interpretation of history. On the other hand, the inheritance of concealing still exists – especially when it comes to oral history.